uGLAD: A Deep Learning Model to Recover Conditional Independence Graphs - Shrivastava, Harsh; Chajewska, Urszula; Abraham, Robin; Chen, Xinshi (Workshop on New Frontiers in Graph Learning (NeurIPS 2022), 2022)
Probabilistic Graphical Models are generative models of complex systems. They rely on conditional independence assumptions between variables to learn sparse representations which can be visualized in a form of a graph. Such models are used for domain exploration and structure discovery in poorly understood domains. This work introduces a novel technique to perform sparse graph recovery by optimizing deep unrolled networks. Assuming that the input data comes from an underlying multivariate Gaussian distribution, we apply a deep model on that outputs the precision matrix. Then, the partial correlation matrix is calculated which can also be interpreted as providing a list of conditional independence assertions holding in the input distribution. Our model, uGLAD, builds upon and extends the state-of-the-art model GLAD to the unsupervised setting. The key benefits of our model are (1) uGLAD automatically optimizes sparsity-related regularization parameters leading to better performance than existing algorithms. (2) We introduce multi-task learning based `consensus' strategy for robust handling of missing data in an unsupervised setting. We evaluate performance on synthetic Gaussian, non-Gaussian data generated from Gene Regulatory Networks, and present case studies in anaerobic digestion and infant mortality. Software: uGLAD Additional discussions: Neurips Talk, Tech Blog